Rapid-Deployment Aortic Valve Replacement in a Real-World All-Comers Population - Yun, Taeyoung; Kim, Kyung Hwan; Sohn, Suk Ho; Kang, Yoonjin; Kim, Ji Seong; Choi, Jae Woong (The Thoracic and Cardiovascular Surgeon, 2022)
Background This study was conducted to evaluate the mid-term outcomes of rapid-deployment aortic valve replacement (AVR) using Edwards Intuity.Methods A total of 215 patients underwent rapid-deployment AVR using Edwards Intuity at our institution. The median follow-up duration was 22 months (interquartile range, 8–36). Primary outcomes were overall survival, cumulative incidence of cardiac death, and major adverse cardiac events. Secondary outcomes were early and 1-year hemodynamic performances of the bioprosthetic valve.Results The mean age was 68.6 ± 10.5 years, and EuroSCORE II was 3.09 ± 4.5. The study population included 113 patients (52.6%) with bicuspid valves (24 patients with type 0 bicuspid valves), 20 patients (9.3%) with pure aortic regurgitation, and 3 patients (1.4%) with infective endocarditis. Isolated AVR was performed in 70 patients (32.4%) and concomitant procedures were performed in 146 patients (67.6%), including aorta surgery (42.3%) and mitral valve procedure (22.3%). Operative mortality was 2.8%. Complete atrioventricular block occurred in 12 patients, but most of them were transient and only 3 patients received permanent pacemaker implantation before discharge. Overall survival at 3 years was 92.3%. Early hemodynamic data showed mean pressure gradients of 15.5 ± 5.0 and 12.7 ± 4.2 mm Hg in the 19 and 21 mm valve, respectively. One-year hemodynamics were also excellent with mean pressure gradients of 14.7 ± 5.3 and 10.7 ± 3.6 mm Hg in the 19 and 21 mm valve, respectively.Conclusion Based on a real-world all-comers population, rapid-deployment AVR using Edwards Intuity could be performed for various indications, including bicuspid valve, pure aortic regurgitation, and infective endocarditis, and the clinical and hemodynamic outcomes were excellent.
Keywords: aortic valve replacement; rapid deployment valve; hemodynamics; outcomes